α-Synuclein aggregation modulation: An emerging approach for the treatment of Parkinson's disease - Singh S.K.; Dutta A.; Modi G. (My University, 2025)
Parkinson's disease (PD) is a multifactorial progressive neurological disorder. Pathological hallmarks of PD are characterized by the presence of α-synuclein (αSyn) aggregates known as Lewy bodies. αSyn aggregation is one of the leading causes for the neuronal dysfunction and death in PD. It is also associated with neurotransmitter and calcium release. Current therapies of PD are limited to only symptomatic relief without addressing the underlying pathogenic factors of the disease process such as aggregation of αSyn. Consequently, the progression of the disease continues with the current therapies. Therefore, the modulation of αSyn aggregation is an emerging approach as a novel therapeutic target to treat PD. There are two major aspects that might be targeted therapeutically: first, protein is prone to aggregation, therefore, anti-aggregative or compounds that can break the pre-existing aggregates should be helpful. Second, there are number of molecular events that may be targeted to combat the disease. © 2017 Future Science Ltd.